2014
DOI: 10.1007/s00604-014-1408-1
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles for the bare-eye based and spectrophotometric detection of proteins, polynucleotides and DNA

Abstract: We have explored the potential of using gold nanoparticles (Au-NPs) in optical and bare-eye discrimination of (a) proteins (such as bovine serum albumin and lysozyme), (b) homo-polynucleotides (such as poly-adenylic acid, polycytidylic acid, poly-uridylic acid and poly-inosinic acid), and (c) long chain DNA (from salmon, herring and thym). Such biomacromolecules can be detected and discriminated due to their ability to prevent the formation of blue aggregates from red (non-aggregated) citrate capped Au-NPs on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 39 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…They offer a large surface to volume ratio due to that nanoscale size, unique electron transfer ability, and great biocompatibility [ 271 ]. AuNPs also can be handily conjugated with many biomolecules without affecting their respective biochemical activities [ 272 ]. Thiolation of respective biomolecules, e.g., oligonucleotides (DNA-AuNPs) is probably the most simple and best way to attach biomolecules to AgNPs through a self-assembled monolayer (SAM) [ 273 ].…”
Section: Miniaturisation Of Electrochemical Biosensorsmentioning
confidence: 99%
“…They offer a large surface to volume ratio due to that nanoscale size, unique electron transfer ability, and great biocompatibility [ 271 ]. AuNPs also can be handily conjugated with many biomolecules without affecting their respective biochemical activities [ 272 ]. Thiolation of respective biomolecules, e.g., oligonucleotides (DNA-AuNPs) is probably the most simple and best way to attach biomolecules to AgNPs through a self-assembled monolayer (SAM) [ 273 ].…”
Section: Miniaturisation Of Electrochemical Biosensorsmentioning
confidence: 99%
“…Thus, similar analyses were performed using two different media used for cell culture (Figure 2C). This experiment was also motivated because the role of protein loading cannot be predicted since it is dependent on the protein and the eventual binding with small molecules, as shown for gold NP (Coglitore et al, 2018;Lepoitevin et al, 2015) or clay mineral (Trigueiro et al, 2018).…”
Section: B Colloidal Stability Of Tio2 Nps With and Without Protein Loadingmentioning
confidence: 99%
“…This is enhanced by the presence of salt in the media (Allouni et al, 2009). The ability of proteins to prevent nanoparticle aggregation is well known (Lepoitevin et al, 2015). For noble metals, such property is modulated to design colorimetric sensors (Sabela et al, 2017).…”
mentioning
confidence: 99%
“…Although some studies have suggested that the adhesion of particular proteins could enhance the circulation times of certain NPs by reducing unspecific cellular uptake [4,5], normally, the opsonization process and recognition by the reticulo-endothelial system (RES) substantially shorten the circulation times of nanomedicines in blood, reducing the possibility of them realizing their function, as shown in Figure 1 [6,7]. Hence, understanding the interaction between proteins and NPs or surfaces is a major field of research, for which a plethora of techniques are being developed [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%